OECD tourism trends and policies 2016. - (:unkn) unknown (My University, 2016)
Die Tourismusbranche macht in OECD-Ländern 4,1 Prozent des Bruttoinlandsprodukts aus und stellt 5,9 Prozent aller Beschäftigten. Allerdings sieht sie sich auch Herausforderungen gegenüber wie immer größeren internationalen Touristenströmen, neuen Verbrauchertrends, der Digitalisierung der Wirtschaft, Sicherheitsproblemen und der Anpassung an den Klimawandel. In der Arbeit wird dargestellt, wie Regierungen Wettbewerb, Innovation und Wachstum in der Tourismusbranche fördern. Zwei Kapitel widmen sich den Themen Transport und der "Sharing Economy".

Tourism Trends and Policies, published biennially, analyses tourism performance and major policy trends, initiatives and reforms across 50 OECD countries and partner economies, providing up-to-date tourism data and analysis. The report is an international reference and benchmark on how effectively countries are supporting competitiveness, innovation and growth in tourism. Tourism has successfully weathered the effects of the global economic crisis, and active tourism policies have played an essential role in supporting a competitive and sustainable tourism economy. The 2016 edition captures these ongoing trends - presenting standardised data covering domestic, inbound and outbound tourism, enterprises and employment, and internal tourism consumption - and reports on how seamless transport can enhance the tourism experience, as well as the opportunities, challenges and implications of the sharing economy for tourism
Keywords: Fremdenverkehr; Wirtschaftszweig; Wirtschaftsentwicklung; Prognose; Verbraucherverhalten; Freizeitverkehr; Tourismus; Trend; Wirtschaftsstatistik; Digitalisierung; Klimaanpassung; Sharing economy